A New Model for Esker Formation Sheds Light on the Processes Within Subglacial Tunnels. Issue 3 (13th March 2019) - Arnold, Neil
Abstract: Eskers are long sedimentary ridges that are widespread in current and previously glaciated landscapes. Eskers are believed to form when sediment carried by glacial meltwater gets deposited in subglacial tunnels, which given the importance of subglacial water for ice dynamics means that eskers can provide important information about the shape and dynamics of ice sheets and glaciers. To date, however, no physical model for their formation has been developed. Beaud et al. (2018, https://doi.org/10.1029/2018JF004779 ) present the first such model; they have linked an existing model for subglacial water flow with one for sediment transport, erosion, and deposition in mixed sediment/bedrock streams. The results of the model add new insights into the conditions which promote esker formation, the rate of supply of sediment to proglacial environments, and also suggest possible links between the water flow regime and the likely esker morphology. Plain Language Summary: This commentary discusses the paper by Beaud et al. (2018) which presents the first numerical, physically based model for esker formation. Eskers are long sedimentary ridges that are widespread in current and previously glaciated landscapes. They are believed to form within subglacial tunnels; this commentary discusses the importance of the configuration of the "plumbing system" of glaciers and ice sheets for their flow patterns and highlights how the model could change how esker deposits are interpreted and how the model results could be used to help infer subglacial water flow characteristics from eskers. Key Points: A new model for esker formation by Beaud et al. (2018) links sediment processes with subglacial tunnel dynamics The model shows sediment deposition as eskers is caused by a bottleneck in sediment transport near the snout of glaciers The model develops realistic sedimentation patterns and will allow better understanding of the links between esker formation and ice dynamics